2020
DOI: 10.2478/emj-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Essential competencies for engineers from the perspective of fresh graduates

Abstract: Determining the competencies required for engineering programmes has become important due to the increasing challenges faced by engineers after graduation and the tremendous development in technology. This research aims to identify the general competencies that fresh graduate students of engineering schools in Jordan believe they need to become competent and effective in their profession as engineers. This study was the first of its kind with students as respondents, and it was the first study of this kind in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Collaboration and teamworking, as well as managing and leading emerged as the mostrelevant competences within the eight groups of categories of generic competences cited by students enrolled in an elective leadership course as important for the development of their professional career. The combination of teamwork and adequate communication skills was seen as having priority among the competences that a naval engineer should master, affirming the results of previous studies (Male et al, 2011;Suleiman & Abahre, 2020). However, using authority, respect and compromise when working in teams was considered less important, in contrast to a study by Newport and Elms (1997).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Collaboration and teamworking, as well as managing and leading emerged as the mostrelevant competences within the eight groups of categories of generic competences cited by students enrolled in an elective leadership course as important for the development of their professional career. The combination of teamwork and adequate communication skills was seen as having priority among the competences that a naval engineer should master, affirming the results of previous studies (Male et al, 2011;Suleiman & Abahre, 2020). However, using authority, respect and compromise when working in teams was considered less important, in contrast to a study by Newport and Elms (1997).…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have identified leadership-related competences such as leading, coordinating and supervising (Suleiman & Abahre, 2020). However, our findings specifically add the importance of leadership style when using personal resources to adapt to different situations, thus contributing to the significance of working on leadership-style adaptation and behaviours in the engineering profession.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The authors of the article understand competences as the knowledge and skills that are indispensable for carrying out specific tasks in an effective way [Volpentesta, Felicetti, 2011;Gudanowska et al, 2020]. In line with [Suleiman, Abahre, 2020], the authors of the article perceive competences as personal dispositional capabilities used to act successfully in new situations. The literature review implies that a multitude of competences are considered essential or at least useful for future-oriented entrepreneurs.…”
Section: Reviewing and Synthetizing Studies University Curricula Courses And Case Studies To Extract Futures Literacy Foresight And Entrementioning
confidence: 96%